ANALYSIS OF THE HOTEL SERVICES MARKET IN THE REPUBLIC OF UZBEKISTAN (Marketing Journal, 2025)
This article examines the current trends in the development of the hotel services market in Uzbekistan. It analyzes the dynamics of changes in the country’s hotel stock and presents the structure of hotels by category and type of accommodation. Key issues and prospects of the sector are identified, tak ing into account global trends and the strategic goals for tourism development in the republic. Proposals are formulated to improve the quality of hotel services and the competitiveness of Uzbekistan’s hotel business in the context of globalization and digitalization.
Keywords: hotel services; market; tourism; Uzbekistan; service quality; hotel classification